«YASHIL URBANIZM» – ZAMONAVIY SHAHARLAR RIVOJLANISHINING ASOSIY YO'NALISHI SIFATIDA - Tashtayeva, S.K.; Yoqubov, O. (SCIENCE and SOCIETY, 2022)
The article reveals the essence of the concept of green urbanism. The studies carried out in this area in the world and their main content are described. The basic principles of green urbanism and practical measures and tasks implemented in the world and Uzbekistan within this framework are being explored.
Keywords: the concept of sustainable urban development; green urbanism; city; urban planning; ecopolis; urban transport; biophilic urbanism